An assessment of the performance appraisal for immigration officers of the Department of Home Affairs at OR Tambo International Airport - Nkuna-Mavutane, Matthews Eddie (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPA)--Stellenbosch University, 2015.